Harnessing the potential of vulnerability assessments for managing social-ecological systems - Thiault, Lauric; Jupiter, Stacy D.; Johnson, Johanna E.; Cinner, Joshua E.; Jarvis, Rebecca M.; Heron, Scott F.; Maina, Joseph M.; Marshall, Nadine A.; Marshall, Paul A.; Claudet, Joachim (Ecology and society, 2021)
The concept of vulnerability has broadened from initial applications in the fields of risk and hazards, human ecology and resilience to include the management of social-ecological systems (SES). We review how this concept has been operationalized in various contexts and identify opportunities and challenges to apply vulnerability assessments to SES management in the face of social, environmental, and climatic changes. We synthesize these lessons into a 12-step framework to help practitioners scope, design, operationalize, and implement vulnerability assessments that can effectively minimize exposure, reduce sensitivity, and enhance adaptive capacity. We describe the rationale, assumptions, and implications that underlie each step and highlight future directions that are critically needed to further enable vulnerability assessments to address real-world sustainability challenges. These include applying biocultural approaches, building knowledge about SES vulnerability to nonclimate stressors, and anticipating potential trade-offs and maladaptation. The framework presented provides a roadmap for the development of integrated vulnerability assessments that are robust, context-specific, and relevant to the management of SES.